Design of Electrical Setting Protection System Indarung VI Cement Plant (Case Study New Cement Plant Construction at PT Semen Padang) - PRASETYAWAN, DIAN EKA (UNIB Press, 2021)
Along with the rapid development of technology and the development of civilization, electrical energy is very important in all fields. This research will conduct a study on the electrical protection system design of PT Semen Padang's Indarung VI Cement Plant using the ETAP 12.6 software. PT Semen Padang's Indarung VI Cement Plant uses three transformers of 150 / 6.3 kV of 30/35 MVA (ONAN / ONAF) and each Main Substation has substations that will supply all the loads to be used. The power flow study shows that the addition of a capacitor bank and a tap changer setting will improve the power factor and voltage of the system, thereby reducing the power supply sent by PLN. The short circuit study shows that the largest short circuit current, which is 35 kA, can be protected by a circuit breaker with a breaking capacity of 40 kA. The protection system coordination study shows that the results of the overcurrent relay setting can protect the electrical system of Indarung VI Cement Plant selectively and safely.